2015
DOI: 10.1371/journal.pone.0134572
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the 16p11.2 Deletion and Null Cntnap2 Mouse Models of Autism Spectrum Disorder

Abstract: Autism spectrum disorder comprises several neurodevelopmental conditions presenting symptoms in social communication and restricted, repetitive behaviors. A major roadblock for drug development for autism is the lack of robust behavioral signatures predictive of clinical efficacy. To address this issue, we further characterized, in a uniform and rigorous way, mouse models of autism that are of interest because of their construct validity and wide availability to the scientific community. We implemented a broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
132
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(142 citation statements)
references
References 83 publications
10
132
0
Order By: Relevance
“…13 tested only male mice with a broad age range of 12–50 weeks of age, while our battery was conducted using both sexes at younger ages, between 6–16 weeks, to avoid aging as a confounding variable. We also note that several studies of other mouse models with mutations in genes implicated in ASD have not identified deficits in social behaviors 33 , potentially due to evolutionary divergence between mouse and human neurobiology, allele or genetic background differences, or sensitivity of methods used to evaluate ASD-relevant behavior in mice.…”
Section: Discussionmentioning
confidence: 99%
“…13 tested only male mice with a broad age range of 12–50 weeks of age, while our battery was conducted using both sexes at younger ages, between 6–16 weeks, to avoid aging as a confounding variable. We also note that several studies of other mouse models with mutations in genes implicated in ASD have not identified deficits in social behaviors 33 , potentially due to evolutionary divergence between mouse and human neurobiology, allele or genetic background differences, or sensitivity of methods used to evaluate ASD-relevant behavior in mice.…”
Section: Discussionmentioning
confidence: 99%
“…ASD has a 5:1 male predominance (11); partially for this reason, most behavioral studies in mouse models have examined only male animals (28, 59, 62). The ability of an identical cellular depletion to produce such divergent effects in male and female mice draws attention to the importance of examining pathophysiological processes in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Animals in cohort 2 were weaned at 4 weeks of age to match the conditions of the previous study, where later weaning was preferred due to small body size of the animals (Brunner et al . ). Breeding success and pup survival was similar among the four groups.…”
Section: Methodsmentioning
confidence: 97%
“…We provide back‐to‐back characterization of five different models of ASD through our previous companion paper on the first two models, Cntnap2 and 16p11 deletion (Brunner et al . ) and present here the results pertaining to the third, fourth and fifth models, namely two distinct Shank3 knockout (KO) models and the Cacna1c heterozygous (HET) model. We chose these models because of their strong construct validity based on human genetic evidence and because of their widespread use in the scientific community due to their availability through The Jackson's Laboratories as part of the Simons Foundation Autism Repository.…”
mentioning
confidence: 99%